2018
DOI: 10.1371/journal.pone.0192859
|View full text |Cite
|
Sign up to set email alerts
|

18F-fluorodeoxyglucose positron-emission tomography (FDG-PET)-Radiomics of metastatic lymph nodes and primary tumor in non-small cell lung cancer (NSCLC) – A prospective externally validated study

Abstract: BackgroundLymph node stage prior to treatment is strongly related to disease progression and poor prognosis in non-small cell lung cancer (NSCLC). However, few studies have investigated metabolic imaging features derived from pre-radiotherapy 18F-fluorodeoxyglucose (FDG) positron-emission tomography (PET) of metastatic hilar/mediastinal lymph nodes (LNs). We hypothesized that these would provide complementary prognostic information to FDG-PET descriptors to only the primary tumor (tumor).MethodsTwo independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 49 publications
2
46
0
1
Order By: Relevance
“…Carvalho et al . 25 observed improved prediction of overall survival in lung cancer when lymph node PET radiomic features were incorporated. However, the performance of obtained models was generally low, c-index 0.56–0.59.…”
Section: Discussionmentioning
confidence: 94%
“…Carvalho et al . 25 observed improved prediction of overall survival in lung cancer when lymph node PET radiomic features were incorporated. However, the performance of obtained models was generally low, c-index 0.56–0.59.…”
Section: Discussionmentioning
confidence: 94%
“…Keeping in mind these limitations, the evidence supporting the additional value of advanced image features from FDG-PET continues to expand year after year. Several of the most recent studies have used techniques such as external cohort validation [95,96,97], or even machine-learning technique [98,99] and concluded in the usefulness of textural analysis regarding patient management. Several method were also proposed to minimize the effect of inter-center variability related to textural features computation [95,100,101] with encouraging results both on a methodological and prognostic level.…”
Section: Intratumor Heterogeneity Exploration Through Quantitativementioning
confidence: 99%
“…Many studies have shown that radiomics features have great potential to be the maker for tumor phenotype (8)(9)(10)(11)(12)(13)(14)(15)(16)(17), and found Adc can be differentiated from Sqc by radiomics (17)(18)(19)(20)(21)(22)(23). However, The data sets of those studies only included Adc and Sqc, that is to say, the accuracy of those models will be affected by other histological subtypes of lung cancer.…”
Section: Discussionmentioning
confidence: 99%